The legacy of literary reflexivity; or, the benefits of doubt. Issue 10 (3rd October 2022) - Tanner, Julie
ABSTRACT: Literary reflexivity entered the twenty-first century trailed by a cluster of negative connotations and affects. Precipitated by popular distaste for postmodern metafiction, this bad reputation has been reinforced by the recent backlash against autofiction, which faces similar charges of narcissism, plotlessness, and unfeeling; altogether another crisis for the novel. Meanwhile, reflexivity – writing that reflects upon its own composition – remains a firm stalwart of contemporary writing. This article surveys the unique dynamics of reflexivity's detractors and practitioners (these groups converge occasionally), contending that writing about writing persists due to its special relationship with doubt. Reflexivity necessarily leaves itself open to both criticism and reinterpretation by its very nature, providing a similarly reflexive set of possibilities for writers and readers to navigate. Reading Giorgio Agamben's 'before of the book' essay and Lydia Davis's novel The End of the Story alongside her notion of 'form as response to doubt' illuminates a more positive contemporary construal for self-reflexive writing beyond the shadow of postmodern negativity.